MSMEs IN INDONESIA DURING THE COVID-19 PANDEMIC REVIEW BASED ON DARWIN'S THEORY - Didik Joko Pitoyo; Eko Armada Riyanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Indonesia is one of the countries experiencing the COVID-19 pandemic. The impact caused by the COVID-19 pandemic was felt for MSMEs, which previously in 2018 were a business group that experienced a significant increase. Changes in consumer behavior due to the pandemic and the ability of MSMEs to follow developments are one of the reasons that caused MSMEs to slump during the COVID-19 pandemic. Very drastic changes are closely related to Darwin's theory which explains the existence of evolution and demands the ability to adapt in self-defense. Changes in business models lead MSMEs to adapt into digital-based businesses to be able to maintain business continuity in the midst of the COVID-19 pandemic.